From Normative to Reflective Collectivism: Discourses on Rewang Across Generations in Javanese Society - Dinna Surya Adi Lestari; Jefri Setyawan (Universitas Muhammadiyah Surakarta, 2025)
Changes in values and participation patterns in the tradition of rewang have become a significant issue amidst social development in Javanese society. This study aims to explore the differences in perspectives between the Baby Boomer generation and Generation Z regarding the rewang tradition based on six collectivism aspects. The subjects consisted of three Baby Boomer women aged 61-79 and twenty Generation Z individuals aged 13-28, recruited using purposive sampling based on their involvement and knowledge of rewang. A qualitative approach was employed, with data collected through focus group discussions, open-ended questionnaires, and analysis of comments on short films and social media videos related to rewang. The data were analyzed thematically. Findings revealed that Baby Boomers view rewang as an essential part of social identity and collective obligation, while Generation Z interprets it contextually, considering efficiency and personal autonomy. These results indicate that collectivist values persist but adapt according to social dynamics and generational changes. The study’s implications are vital for developing culturally sensitive preservation strategies that respond to shifting intergenerational values in contemporary society.